Strongyloides stercoralis infection in HIV-positive men who have sex with men. (April 2020) - Ross, Sophie A; Pintilie, Hannah; Hatcher, James; Dosekun, Olamide; Cooke, Graham S; Bailey, Angela C
Strongyloides stercoralis is a common parasitic infection in tropical and subtropical areas which may result in fatal hyperinfection syndrome in immunosuppressed patients. Infection occurs through skin or mucous membrane contact with material contaminated with infected human faeces. Sexual transmission of other gastrointestinal infections has been observed in men who have sex with men (MSM), with human immunodeficiency virus (HIV) a known risk factor. We present a case series of strongyloidiasis in seven HIV-positive MSM living in a non-endemic area. We found high rates of concomitant sexually transmitted infection and chemsex drug use, suggesting high-risk sexual behaviour.